2016
DOI: 10.1134/s000629791606002x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 metallothionein (ZjMT) is responsible for heavy metal tolerance in Ziziphus jujuba

Abstract: Metallothioneins (MTs) are a family of low molecular weight, cysteine-rich, metal-binding proteins that are able to make cells to uptake heavy metals from the environment. Molecular and functional characterization of this gene family improves understanding of the mechanisms underlying heavy metal tolerance in higher organisms. In this study, a cDNA clone, encoding 74-a.a. metallothionein type 1 protein (ZjMT), was isolated from the cDNA library of Ziziphus jujuba. At the N- and C-terminals of the deduced amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…However, the role of different types of MTs as metal chelators has been identified, which can lead to the tolerance and accumulation of heavy metals in plants [238]. MTs have a great tendency to bind to heavy metals containing Cd, Zn, Cu, and As, and can eliminate them even at a low amount; nevertheless, in terms of the importance as a Cd chelator, MT is considered after PCs [242]. Generally, MTs play multiple roles in plants, such as tolerance and maintenance of the cellular ion balance by detoxification of heavy metals, ROS scavenging, damaged DNA repair, and as well as various physiological processes, including seed germination and fruit ripening in plants [240,243].…”
Section: Phytochelatins and Metallothionein For Cadmium Phytoremediationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the role of different types of MTs as metal chelators has been identified, which can lead to the tolerance and accumulation of heavy metals in plants [238]. MTs have a great tendency to bind to heavy metals containing Cd, Zn, Cu, and As, and can eliminate them even at a low amount; nevertheless, in terms of the importance as a Cd chelator, MT is considered after PCs [242]. Generally, MTs play multiple roles in plants, such as tolerance and maintenance of the cellular ion balance by detoxification of heavy metals, ROS scavenging, damaged DNA repair, and as well as various physiological processes, including seed germination and fruit ripening in plants [240,243].…”
Section: Phytochelatins and Metallothionein For Cadmium Phytoremediationmentioning
confidence: 99%
“…It has been established that MT2, in Coptis japonica, has 14 Cys-residues in its C-and N-terminal that can bind to four Cd(II) ions [239]. Li et al [242], proved that in Ziziphus jujuba 24 h after Cd exposure, ZjMTs levels elevated and caused increased Cd tolerance and detoxification. This MTs also has six Cys residues in the C-and N-terminal structure and belongs to the MT-Type1 group [242].…”
Section: Phytochelatins and Metallothionein For Cadmium Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the bioaccumulation properties of RmMT were assessed using transformed E. coli BL21, and the results indicated that the recombinant protein RmMT could chelate multiple heavy metals in the following order of preference: Cu 2+ > Pb 2+ > Zn 2+ > Cd 2+ > Ag + (Figure ). It was observed that ZjMT gene from plant Ziziphus jujube displayed higher bioaccumulation ability of essential and nonessential metal ions compared with control cells in E. coli . These results prove that the functional contribution of MTs to metal detoxification and homeostasis was most likely through their ability to bind different metal ions .…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have reported that MT genes could enhance metal accumulation capacity in different organisms . Zhang et al transferred SaMT2 gene (from plant Sedum alfredii Hance) into yeast and tobacco and found that the expression of the MT gene enhanced Cd and Zn accumulation in the transgenic organisms.…”
Section: Discussionmentioning
confidence: 99%